Five men posing against a rock wall near Black Lake, White Pass Trail, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Photographs taken by Asahel Curtis during his trip to the Klondike in 1897-1899. Caption on image: Curtis 213 Handwritten on verso: Around Black Lake. From Washington State Historical Society: Black Lake along Skagway Trail. PH Coll 519.213 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number